An unusual presentation of primary renal lymphoma: A case report - Shah, Darshil; R, Neelakandan; T, Chandru; K, Natarajan (Indian Journal of Case Reports, 2019)
Lymphomatous involvement of the kidney is often seen as a part of the disseminated disease but primary renal lymphoma is very rare. It is essential to differentiate between renal cell carcinoma and renal lymphoma in patients presenting with renal masses. The prognosis is usually poor with a median survival less than a year. We present the case of a 81-year-old male who presented with type B symptoms and was diagnosed to have primary lymphoma of the kidney and discuss briefly about the primary renal lymphoma.